Determinan Kapasitas Pendapatan Asli Daerah (PAD) di Kabupaten/Kota Provinsi Kalimantan Timur Tahun 2015-2019 - Fahrul Anam; Hendra Kusuma (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to determine the effect of Regional Tax, Population, and GRDP on Regional Original Income. The data used in this study is secondary data for the 2015-2019 period. Regional Original Income is the dependent variable, while Local Tax, Population, and GRDP are independent variables. The data collection technique uses documentation study techniques. The research method used is panel data regression analysis. The results of this study are that Regional Tax has a positive and significant effect on PAD, Population has a positive and significant impact on PAD, and GRDP has a positive and significant effects on PAD.